Barriers and facilitating factors for research involvement in cancer centers: a survey of colorectal cancer center coordinators in Germany, Austria, and Switzerland - Kowalski, Christoph; Post, Stefan (Cancer control, 2018)
Improvements in health care depend on research involving health-care providers (HCPs) and health-care organizations (HCOs). Existing research suggests that involvement in research studies is still much lower than it could be. This study investigates factors that may impede or facilitate research involvement.
Article first published online: March 28, 2018
Gesehen am 29.01.2020